Treatment of spent filter backwash water from systems for treatment of water of swimming-pools and baths : english translation of DIN 19645:2016-07 (Beuth Verlag, 2016)
Guidelines that focus on swimming pool and bath water filtration systems, waste water and environmental health. Intended for the professional public.
Keywords: environmentální zdraví; Filtration; koupele; Swimming Pools; filtrace; environmentální vědy; odpadní voda; Baths; čištění vody; plavecké bazény; Water Purification; Wastewater; Environmental Health